2015
DOI: 10.1016/j.ijpharm.2015.07.076
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of spray drying, electroblowing and electrospinning for preparation of Eudragit E and itraconazole solid dispersions

Abstract: Three solvent based methods: spray drying (SD), electrospinning (ES) and air-assisted electrospinning (electroblowing; EB) were used to prepare solid dispersions of itraconazole and Eudragit E. Samples with the same API/polymer ratios were prepared in order to make the three technologies comparable. The structure and morphology of solid dispersions were identified by scanning electron microscopy and solid phase analytical methods such as, X-ray powder diffraction (XRPD), differential scanning calorimetry (DSC)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(21 citation statements)
references
References 38 publications
(37 reference statements)
2
19
0
Order By: Relevance
“…In PM with a mount of the polymer (1:5 ratio), no diffraction peaks were discovered due to the polymer dilution effect [ 32 , 33 ]. The disappearance of characteristic peaks in all SDs suggested a significant decrease in wogonin crystallinity, demonstrating a drug amorphization or its solvation in the amorphous carriers [ 5 , 33 , 34 ]. DSC analysis enables the quantitative detection of all processes in which energy is required or produced.…”
Section: Discussionmentioning
confidence: 99%
“…In PM with a mount of the polymer (1:5 ratio), no diffraction peaks were discovered due to the polymer dilution effect [ 32 , 33 ]. The disappearance of characteristic peaks in all SDs suggested a significant decrease in wogonin crystallinity, demonstrating a drug amorphization or its solvation in the amorphous carriers [ 5 , 33 , 34 ]. DSC analysis enables the quantitative detection of all processes in which energy is required or produced.…”
Section: Discussionmentioning
confidence: 99%
“…However, no notable increase in productivity has been reported using multiple needles, and presumably it is the reason why these methods did not spread in practical usage. Much higher production rates can be achieved with electroblowing (Figure e) when an additional air flow facilitates the solvent evaporation (Armantrout, Bryner, & Spiers, ; Balogh et al, ; Kakoria & Sinha‐Ray, ; Medeiros, Glenn, Klamczynski, Orts, & Mattoso, ; Pokorny, Rassushin, Wolfova, & Velebny, ; Sóti et al, ). Although the feeding rate is increased during the electroblowing process, beads or droplets can also appear among the fibers more frequently due to the effects of the air flow.…”
Section: Scaled‐up Es Technologiesmentioning
confidence: 99%
“…In this work, the air‐assisted method was successfully applied for preparing fibrous diclofenac sodium‐cyclodextrin complex‐based reconstitution injection. Even higher feeding rate was reached with electroblowing in the case of itraconazole‐loaded samples (Sóti et al, ). In this work, the authors compared electroblowing to spray drying and they not only showed that increased productivity (50 g/hr) is achievable using the air‐assisted technology, but they also demonstrated that the prepared amorphous solid dispersion showed better stability than the spray‐dried samples.…”
Section: Applications Of Scaled‐up Es In the Pharmaceutical Industrymentioning
confidence: 99%
“…There exist a range of other routes to preparing SDs and ASDs, with the most commonly applied being hot melt extrusion (HME), spray drying and freeze drying. [10][11][12][13] All these technologies have great utility in the pharmaceutical industry, and there are marketed products fabricated using all three. However, all have fundamental disadvantages associated with them.…”
Section: Introductionmentioning
confidence: 99%